Titanium oxide / carbon material composite absorbent as well as preparation method and application thereof
By controlling the composite of TixO2x-1 particles and carbon materials at high temperatures, the problems of difficult phase synthesis and impedance mismatch in the titanium oxide/carbon material composite absorber are solved, and excellent electromagnetic wave absorption capacity and electromagnetic attenuation characteristics are achieved, which are suitable for electromagnetic protection and microwave stealth.
Patent Information
- Application Number
- CN202510054814.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-14
- Publication Date
- 2025-04-29
AI Technical Summary
In the prior art, the synthesis of titanium oxide phase in the composite absorber of titanium oxide/carbon materials is difficult, the large particle size is not conducive to microwave absorption, and the impedance mismatch caused by high conductivity of a single carbon material.
By controlling the component design of TixO2x-1 particles and the concentration of oxygen vacancies at high temperature of hydrogen, combined with the composite of carbon materials, a TixO2x-1/carbon material composite absorber with excellent electromagnetic wave absorption capacity was prepared.
It improves the electromagnetic wave absorption capacity of TixO2x-1/carbon materials, improves impedance matching and electromagnetic attenuation characteristics, and is suitable for electromagnetic protection and microwave stealth fields.
Smart Images

Figure CN119899636A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of absorbing materials, and in particular to a titanium oxide / carbon material composite absorber and a preparation method and application thereof. Background Art
[0002] At present, the rapid development of wireless electronic devices in the era of 5G communication and big data has brought convenience to human life, but the serious electromagnetic radiation pollution problem caused by it cannot be ignored. To solve this problem, a simple and effective strategy is to design semiconductor absorbers with defects / heterogeneous interfaces. Due to the excellent polarization / conduction loss, semiconductor absorbers show excellent electromagnetic absorption ability.
[0003] Among the reported electromagnetic wave absorbing materials, oxide semiconductors, such as Cu2O, SnO2, MoO3, V2O5, ZnO, TiO2, Fe2O3, ZrO2, CoO, WO3, In2O3, Al2O3 and Fe3O4, have attracted many scientists to study the relevant dielectric and microwave absorption properties. Although these semiconductor absorbing composite materials have been deeply studied from various aspects of component compounding and structural optimization, this type of oxide semiconductor mainly focuses on the influence of microstructure rather than atomic level on absorbing performance. Therefore, it is very important to choose a dielectric absorber with good absorption capacity.
[0004] Among all suitable candidate materials, multiphase titanium oxide semiconductors (Ti x O 2x-1 (4≤x≤9)) is due to the lower conductivity (10 -12 ~10 -7 S / cm) of TiO2, first discovered by Arne Magnéli in 1957. Unlike single-phase TiO2, multiphase Ti x O 2x-1 It has higher conductivity and dielectric constant, more oxygen vacancies and narrower band gap. Similarly, the introduction of oxygen vacancies in titanium oxide increases the charge density near the valence band of the semiconductor, changes the intrinsic band gap of titanium oxide, and makes the abundant localized electrons in titanium oxide form more dipole polarization, which also improves the conductivity and dielectric constant of the semiconductor. According to theoretical analysis, due to the absence of oxygen atoms, oxygen vacancies are generated, and the periodic potential field generated by the strict periodic arrangement of atoms will be destroyed, and it is possible to introduce energy levels that electrons can reach in the forbidden band. For p-type semiconductors, the introduction of oxygen vacancies increases the area near the valence band, that is, Ti x O 2x-1 From Ti 4+ To Ti 3+(4≤x≤9) charge density changes the intrinsic band gap of the semiconductor. The ability of oxygen vacancies to close the band gap between the Fermi level and the valence band determines the conductivity of p-type semiconductors. The relationship between conductivity (σ) and dielectric constant (ε″) can be expressed by free electron theory: ε″=σ / 2πε0f, where f and ε0 are the frequency and dielectric constant in a vacuum, respectively. Therefore, related electromagnetic properties including ε' and ε″ can be indirectly reflected by the band structure of defective semiconductors.
[0005] In summary, the composite of multiphase titanium oxide semiconductor and single high dielectric carbon material carbon black, carbon fiber, carbon nanotube and graphene can effectively improve the material impedance matching and multiple loss mechanisms, thereby obtaining Ti with excellent microwave absorption performance. x O 2x-1 / carbon material composite absorbent.
[0006] In "Zichao Mo, Rongliang Yang, Dongwei Lu, Leilei Yang, Qingmei Hu, Hongbian Li, Hai Zhu, Zikang Tang, Xuchun Gui. Lightweight, three-dimensional carbon Nanotube@TiO2 sponge with enhanced microwave absorption performance" (Carbon, 2019, 144, 433-439), a preparation method of a three-dimensional carbon nanotube@TiO2 sponge composite material and its application in the field of electromagnetic wave absorption are disclosed. The following technical features are specifically disclosed: using ferrocene / dichlorobenzene solution as a carbon source, carbon nanotube sponge is synthesized by chemical vapor deposition, the concentration of ferrocene in the precursor is 200 mg / mL, the reaction temperature is 860°C, and the flow rates of Ar and H2 mixed gases are set to 2000sccm and 300sccm, respectively. The obtained sponge was immersed in a tetrabutyl titanate / anhydrous ethanol solution with a concentration of 0.1-0.5 g / mL, and then the filled sponge was transferred to water and ultrasonicated for 40 minutes, where the TiO2 precursor was hydrolyzed to form an amorphous TiO2 layer on the surface of each carbon nanotube in the sponge. After freeze drying for 12 hours, a carbon nanotube @TiO2 sponge was obtained, in which the carbon nanotubes uniformly wrapped the TiO2 layer to form a core-shell structure. In order to optimize the microwave absorption performance, it is necessary to convert amorphous TiO2 into crystalline TiO2. The carbon nanotube @TiO2 sponge was annealed at 200-800℃ in Ar for 2h to obtain a CNT@TiO2 sponge containing different TiO2 crystal phases. Finally, in order to adjust the dielectric properties of the sample, the carbon nanotube @TiO2 sponge was heat treated in air at 360-440℃ for 2-6h to remove some carbon nanotubes. However, the preparation method proposed in this document is complicated and its absorbing ability is limited. When the thickness of the absorbing layer is 2 mm, the minimum reflection loss value of the three-dimensional carbon nanotube@TiO2 sponge composite material is only -31.8 dB, and the corresponding effective bandwidth is 2.7 GHz.
[0007] In "Hongsheng Liang, Jiaolong Liu, Yi Zhang, Lei Luo, Hongjing Wu. Ultra-thin broccoli-like SCFs@TiO2 one-dimensional electromagnetic wave absorbing material." (Composites Part B, 2019, 178, 107507), a method for preparing an ultra-thin broccoli-like SCFs@TiO2 composite material and its application in the field of electromagnetic wave absorption are disclosed. The following technical features are specifically disclosed: 15mL of concentrated hydrochloric acid (37%) is diluted with 15mL of ultrapure water and mixed with a solution containing 0.5g of short carbon fibers (SCFs) and 0.1ml of 0.2mol / LTiCl4 aqueous solution. 0.1mL of titanium isopropoxide is added to the above solution, stirred for 0.5h, and then transferred to a 100mL stainless steel autoclave and hydrothermally treated at 180°C for 3h. The prepared product is washed and filtered several times and dried at 80°C under vacuum for 12h. The product is calcined in air at 550°C for 1h. The TiO2 particles have low electrical conductivity and low dielectric loss, which is not conducive to the dissipation of electromagnetic waves.
[0008] In "Core-shell structure Ti4O7 / magnetic metal composite absorber and preparation method thereof" (patent number ZL202110642797.5, authorization announcement date September 27, 2022), a preparation method of a core-shell structure Ti4O7 / magnetic metal composite material and its application in the field of electromagnetic wave absorption are disclosed. The following technical features are specifically disclosed: When preparing the TiO2 precursor, 1mL of titanium isopropoxide, 40-60mL of anhydrous ethanol and 10-20mL of glacial acetic acid are stirred at 60-100°C for 1h, and hydrochloric acid HCl is added dropwise to adjust the pH value of the solution to 1-3. The solution is transferred to a polytetrafluoroethylene reactor. The reactor is transferred to a drying oven and heated to 160-200°C at a heating rate of 5-10°C / min; the temperature is kept for 4-8h to obtain a TiO2 precursor. The obtained TiO2 precursor is placed in a tubular furnace and hydrogen is introduced as a protective gas. Heat to 1000℃ at a heating rate of 5° / min and keep warm for 2h. After the insulation is completed, cool with the furnace. Obtain Ti4O7 particles. Disperse the obtained Ti4O7 particles, water-soluble metal salts, and hydrazine hydrate in water, stir evenly, and obtain a Ti4O7 / single magnetic metal salt mixed solution. Among them, Ti4O7: water-soluble metal salt: hydrazine hydrate: water = 1mmol: 1~3mmol: 4~8mL: 40~80mL. Transfer the obtained Ti4O7 / single magnetic metal salt mixed solution to a high-pressure reactor. Place the high-pressure reactor in a drying oven, heat to 150~180℃ at a heating rate of 5~10℃ / min and keep warm for 14~18h, and react the Ti4O7 / magnetic metal salt mixed solution placed in the high-pressure reactor. After the insulation is completed, cool to room temperature with the furnace. Take out the precipitate of the solution after the reaction, wash and dry it, and complete the preparation of the core-shell structure Ti4O7 / magnetic metal composite absorbent. The water-soluble metal salt is Ni salt, Co salt or Fe salt; the prepared Ti4O7 / single magnetic metal composite absorber is divided into Ti4O7 / Ni composite absorber, Ti4O7 / Co composite absorber and Ti4O7 / Fe composite absorber. The Ti4O7 / magnetic metal composite material has a single component and limited wave absorption capacity, which is not conducive to the study of electromagnetic wave absorption performance. Summary of the invention
[0009] In view of the deficiencies in the above-mentioned background technology, the present invention mainly solves the problems in the prior art that titanium oxide phase synthesis is difficult in titanium oxide / carbon material composite absorbents, large particle size is not conducive to microwave absorption, and high conductivity of single carbon material leads to impedance mismatch. The present invention provides a titanium oxide / carbon material composite absorbent and its preparation method and application. The method regulates the Ti x O 2x-1 The particle composition design and oxygen vacancy concentration overcome the shortcomings of low conductivity and low dielectric loss of single TiO2 material, thereby improving Tix O 2x-1 / Electromagnetic wave absorption capacity of carbon materials.
[0010] The first object of the present invention is to provide a titanium oxide / carbon material composite absorbent, the absorbent comprising Ti x O 2x-1 As a substrate, and a carbon material composited on the substrate; x = 1 to 10;
[0011] The content of the matrix is 50-99wt.%, the content of the carbon material is 50-1wt.%, and the sum of the percentages of the matrix and the carbon material is 100%.
[0012] Preferably, the carbon material is carbon fiber, carbon nanotube or graphene.
[0013] Preferably, the particle size of the carbon material is 1 to 10 μm; x O 2x-1 The particle size of the particles is 50 to 100 nm.
[0014] The second object of the present invention is to provide a method for preparing a titanium oxide / carbon material composite absorbent, comprising the following steps:
[0015] Dispersing tetrabutyl titanate, carbon material, acetic acid and concentrated nitric acid in anhydrous ethanol, stirring evenly to obtain a mixed solution;
[0016] The mixed solution is transferred to a reaction kettle and kept at 160-200°C for 4-8 hours to obtain a TiO2 / carbon material precursor;
[0017] The TiO2 / carbon material precursor is placed in a tubular furnace and kept warm at 800-1100°C for 2-8 hours in a hydrogen atmosphere to obtain a titanium oxide / carbon material composite absorbent.
[0018] Preferably, the usage ratio of tetrabutyl titanate, carbon material, acetic acid, concentrated nitric acid and anhydrous ethanol is 1 g: 0.01-2 g: 10-20 mL: 2-5 mL:: 40-60 mL.
[0019] Preferably, the heating rate for transferring the mixed solution to the reaction kettle is 5-10° C. / min.
[0020] Preferably, the TiO2 / carbon material precursor is placed in a tube furnace at a heating rate of 8 to 12° / min.
[0021] The third object of the present invention is to provide a titanium oxide / carbon material composite absorber for use in electromagnetic absorption.
[0022] Compared with the prior art, the present invention has the following beneficial effects:
[0023] The present invention provides a titanium oxide / carbon material composite absorbent and its preparation method and application. The present invention is the first to combine Ti x O 2x-1 / Carbon materials are used in the field of absorbing materials because high conductivity helps to form a higher imaginary part of the dielectric constant, indicating that it has a larger dielectric loss. x O 2x-1 It has strong interface polarization and defect polarization capabilities and is a good candidate for microwave absorbing materials. x O 2x-1 The content ratio of carbon materials effectively improves the impedance matching and electromagnetic attenuation characteristics of the core-shell structure Ti4O7 / magnetic metal composite absorber, and can be widely used as an electromagnetic wave absorption material in the corresponding electromagnetic protection and microwave stealth fields.
[0024] The present invention adopts hydrogen reduction method to prepare Ti x O 2x-1 / carbon material, has the advantages of being simple and efficient; at the same time, the present invention regulates Ti by high temperature of hydrogen x O 2x-1 The particle composition design and oxygen vacancy concentration overcome the shortcomings of low conductivity and low dielectric loss of single TiO2 material, thereby improving Ti x O 2x-1 / Electromagnetic wave absorption capacity of carbon materials.
[0025] The present invention first prepares a TiO2 / single carbon material precursor by a simple and clean hydrothermal reaction, and then obtains TiO2 / single carbon material precursor by high temperature heat treatment. x O 2x-1 / carbon material composite absorbent. Figure 2 The TiO2 / single carbon material composite absorbent is composed of round TiO2 particles uniformly wrapped around carbon nanotubes, wherein the size of TiO2 is between 5-20nm, and the diameter and length of the carbon nanotubes are 20nm and 1-10μm respectively, forming a dense core-shell structure; in addition, Figure 5 It can be seen that the Ti x O 2x-1 / Carbon material is composed of ellipsoidal Ti x O 2x-1 The particles are uniformly loaded around the carbon nanotubes, among which Ti x O 2x-1 The size is between 50 and 100 nm. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 This is the X-ray diffraction pattern of the TiO2 / carbon nanotube composite sample provided in Example 7.
[0027] Figure 2 Ti provided in Example 7 x O 2x-1 / CNTs composite sample.
[0028] Figure 3 This is a scanning electron microscope photograph of the TiO2 / carbon nanotube composite sample provided in Example 7.
[0029] Figure 4 Ti provided in Example 7 x O 2x-1 SEM images of the / carbon nanotube composite sample.
[0030] Figure 5 Schematic diagram of reflection loss of 30 wt.% TiO2 / carbon nanotubes when the absorbing layer thickness is 2 mm provided in Example 7.
[0031] Figure 6 The absorbing layer thickness provided for Example 7 is 2 mm and 30 wt.% Ti x O 2x-1 / Schematic diagram of reflection loss of carbon nanotubes.
[0032] Figure 7 It is a flow chart of the present invention.
[0033] In the figure: 1 is the X-ray diffraction pattern of ICSD#96-901-5930 corresponding to the TiO2 sample; 2 is the X-ray diffraction pattern of the TiO2 / carbon nanotube composite sample; 3 is the X-ray diffraction refinement fitting error curve; 4 is the diffraction peak curve of ICSD#97-001-6297 card corresponding to the Ti4O7 material; 5 is the diffraction peak curve of PDF#96-153-9581 card corresponding to the Ti5O9 material; 6 is the diffraction peak curve of the Ti6O 11 The X-ray diffraction peak curve of ICSD#96-152-1096 corresponding to the substance; 7 is Ti x O 2x-1 / carbon nanotube composite sample corresponding to the X-ray diffraction peak curve. DETAILED DESCRIPTION
[0034] In order to enable those skilled in the art to better understand and implement the technical solution of the present invention, the present invention is further described below in conjunction with specific embodiments and drawings, but the embodiments are not intended to limit the present invention.
[0035] The purpose of the present invention is to provide a titanium oxide / carbon material composite absorbent and a preparation method and application thereof, so as to solve the problem of the deficiency of a single TiO2 material with low dielectric loss and low magnetic loss existing in the prior art.
[0036] In order to achieve the above object, the present invention provides a titanium oxide / carbon material composite absorbent in a first aspect. The absorbent comprises Ti x O 2x-1 As a substrate, and a carbon material composited on the substrate; x = 1 to 10;
[0037] The content of the matrix is 50-99wt.%, the content of the carbon material is 50-1wt.%, and the sum of the percentages of the matrix and the carbon material is 100%.
[0038] Wherein, the carbon material is carbon fiber, carbon nanotube or graphene.
[0039] The particle size of the carbon material is 1 to 10 μm; x O 2x-1 The particle size of the particles is 50 to 100 nm.
[0040] The present invention adopts Ti x O 2x-1 It has strong interface polarization and defect polarization capabilities and is a good candidate for microwave absorbing materials. x O 2x-1 The content ratio of carbon materials effectively improves the impedance matching and electromagnetic attenuation characteristics of the core-shell structure Ti4O7 / magnetic metal composite absorber, and can be widely used as an electromagnetic wave absorption material in the corresponding electromagnetic protection and microwave stealth fields.
[0041] The second aspect of the present invention provides a method for preparing a titanium oxide / carbon material composite absorbent, comprising the following steps:
[0042] Dispersing tetrabutyl titanate, carbon material, acetic acid and concentrated nitric acid in anhydrous ethanol, stirring evenly to obtain a mixed solution;
[0043] The mixed solution is transferred to a reaction kettle and kept at 160-200°C for 4-8 hours to obtain a TiO2 / carbon material precursor;
[0044] The TiO2 / carbon material precursor is placed in a tubular furnace and kept warm at 800-1100°C for 2-8 hours in a hydrogen atmosphere to obtain a titanium oxide / carbon material composite absorbent.
[0045] The usage ratio of tetrabutyl titanate, carbon material, acetic acid, concentrated nitric acid and anhydrous ethanol is 1g: 0.01-2g: 10-20mL: 2-5mL: 40-60mL.
[0046] The temperature of the mixed solution transferred to the reactor is increased at a rate of 5 to 10°C / min. The temperature of the TiO2 / carbon material precursor placed in the tube furnace is increased at a rate of 8 to 12°C / min.
[0047] In one embodiment, a method for preparing a titanium oxide / carbon material composite absorbent comprises:
[0048] Step 1, preparing TiO2 / single carbon material mixed solution:
[0049] Disperse the tetrabutyl titanate, carbon material, acetic acid and concentrated nitric acid in anhydrous ethanol and stir evenly to obtain a TiO2 / single carbon material mixed solution. Among them, tetrabutyl titanate: carbon material: acetic acid: concentrated nitric acid: anhydrous ethanol = 1g: 0.01-2g: 10-20mL: 2-5mL: 40-60mL; preferably, tetrabutyl titanate: carbon material: acetic acid: concentrated nitric acid: anhydrous ethanol = 1g: 1g: 15mL: 3mL: 50mL.
[0050] The carbon material is carbon fiber, carbon nanotube or graphene; the prepared TiO2 / single carbon material mixed solution is divided into TiO2 / carbon fiber mixed solution, TiO2 / carbon nanotube mixed solution and TiO2 / graphene mixed solution.
[0051] When preparing a TiO2 / single carbon material mixed solution, when carbon fiber is used, the tetrabutyl titanate, carbon fiber, acetic acid and concentrated nitric acid are dispersed in anhydrous ethanol and stirred evenly to obtain a TiO2 / carbon fiber mixed solution.
[0052] When carbon nanotubes are used, the tetrabutyl titanate, carbon nanotubes, acetic acid and concentrated nitric acid are dispersed in anhydrous ethanol and stirred evenly to obtain a TiO2 / carbon nanotube mixed solution.
[0053] When carbon fiber is used, the tetrabutyl titanate, graphene, acetic acid and concentrated nitric acid are dispersed in anhydrous ethanol and stirred evenly to obtain a TiO2 / graphene mixed solution.
[0054] It should be noted that the acidity of the system can be adjusted by acetic acid to prevent the titanium ion from hydrolyzing too quickly. Ti(O-C4H9)4 is hydrolyzed in C2H5OH to generate Ti(OH)4, and TiO2 can be obtained after dehydration. The hydrolysis reaction of tetrabutyl titanate in an ethanol medium under acidic conditions is carried out step by step, and the hydrolysis product is a titanium ion sol. After the above sol system is allowed to stand for a period of time, concentrated nitric acid is added to adjust the pH concentration of the solution, and the gelation process is promoted in a water bath environment at 50-80°C, and finally a stable TiO2 gel is formed.
[0055] Step 2, preparing TiO2 / carbon material precursor:
[0056] Transfer the TiO2 / single carbon material mixed solution obtained in step 1 to a high-pressure reactor. Transfer the solution to a polytetrafluoroethylene reactor. Transfer the reactor to a drying oven and heat it to 160-200°C at a heating rate of 5-10°C / min; keep it warm for 4-8 hours to react the TiO2 / single carbon material mixed solution in the high-pressure reactor. After the insulation is completed, cool it to room temperature with the furnace. Take out the precipitate of the solution after the solvent thermal reaction, wash and dry it to obtain a TiO2 / single carbon material precursor.
[0057] The prepared TiO2 / single carbon material precursor is divided into TiO2 / carbon fiber precursor, TiO2 / carbon nanotube precursor and TiO2 / graphene precursor.
[0058] Step 3, Preparation of Ti x O 2x-1 / Single Carbon Material:
[0059] Preparation of the Ti x O 2x-1 / carbon material, the TiO2 / carbon material precursor obtained in step 2 is placed in a tubular furnace, hydrogen is introduced as a protective gas; the temperature is increased to 800-1100°C at a heating rate of 2-10°C / min, and the temperature is kept for 2-8 hours. After the temperature is kept, the furnace is cooled. x O 2x-1 / Carbon materials.
[0060] The prepared Ti x O 2x-1 / Single carbon materials include: TiO2 / carbon fiber composites, TiO2 / carbon nanotube composites or TiO2 / graphene composites.
[0061] A third aspect of the present invention provides a titanium oxide / carbon material composite absorber for use in electromagnetic absorption.
[0062] It should be noted that the experimental methods used in the present invention are all conventional methods unless otherwise specified; the reagents and materials used are all commercially available unless otherwise specified.
[0063] The Ti x O 2x-1 Ti / carbon composite absorbent x O 2x-1 As a matrix, a carbon material is composited on the matrix by solvent thermal reaction. The content of the matrix is 50-99wt.%, and the content of the carbon material is 50-1wt.%; the sum of the percentages is 100%.
[0064] The carbon material is one of carbon fiber, carbon nanotube and graphene.
[0065] The composite absorbent is composed of the carbon material and Ti x O 2x-1 Ti particles are formed by solvothermal reaction x O 2x-1 / carbon material composite absorbent.
[0066] The carbon material is carbon fiber, carbon nanotube or graphene; the diameter of the carbon material is 5 μm. x O 2x-1 The particle size of the particles is 50 to 100 nm.
[0067] Example
[0068] A method for preparing a titanium oxide / carbon material composite absorbent, see Figure 7 As shown, the following steps are included:
[0069] Step 1, preparing a TiO2 / single carbon material mixed solution.
[0070] 1g of titanium isopropoxide, 2g of a single carbon material, 60mL of anhydrous ethanol and 20mL of glacial acetic acid were stirred together at 100°C for 1h, ultrasonically dispersed for 30min, and then hydrochloric acid HCl was added dropwise to adjust the pH value to 3 to obtain a TiO2 / single carbon material mixed solution. The prepared TiO2 / single carbon material mixed solution is divided into a TiO2 / carbon fiber mixed solution, a TiO2 / carbon nanotube mixed solution and a TiO2 / graphene mixed solution.
[0071] Step 2: Prepare TiO2 / carbon material precursor.
[0072] The TiO2 / single carbon material mixed solution was transferred to a polytetrafluoroethylene reactor, and the reactor was transferred to a drying oven, and the temperature was increased to 200°C at a heating rate of 10°C / min; the temperature was kept for 8 hours to obtain a TiO2 / carbon material precursor.
[0073] The prepared TiO2 / carbon material precursor is divided into TiO2 / carbon fiber, TiO2 / carbon nanotube and TiO2 / graphene.
[0074] Step 3: Preparation of Ti x O 2x-1 / Carbon materials.
[0075] The obtained TiO2 / carbon material precursor was placed in a tube furnace and hydrogen was introduced as a protective gas. The temperature was raised to 1100°C at a heating rate of 10°C / min and kept at this temperature for 2 hours. After the heat preservation was completed, the furnace was cooled. x O 2x-1 / Carbon materials.
[0076] The prepared Tix O 2x-1 / Carbon materials are divided into Ti x O 2x-1 / Carbon fiber, Ti x O 2x-1 / Carbon nanotubes and Ti x O 2x-1 / Three types of graphene.
[0077] The components of each example are shown in Table 1.
[0078] Table 1 Components of each embodiment
[0079] Example Matrix Content wt.% Particle size nm Carbon Materials Content wt.% Particle size μm 1 <![CDATA[Ti x THE 2x-1 ]]> 50 50 Carbon Fiber 50 5 2 <![CDATA[Ti x THE 2x-1 ]]> 99 100 Carbon Fiber 1 5 3 <![CDATA[Ti x THE 2x-1 ]]> 85 85 Carbon Fiber 15 5 4 <![CDATA[Ti x THE 2x-1 ]]> 75 75 Carbon Nanotubes 25 5 5 <![CDATA[Ti x THE 2x-1 ]]> 92 92 Carbon Nanotubes 8 5 6 <![CDATA[Ti x THE 2x-1 ]]> 65 60 Carbon Nanotubes 35 5 7 <![CDATA[Ti x THE 2x-1 ]]> 70 70 Graphene 30 5 8 <![CDATA[Ti x THE 2x-1 ]]> 90 90 Graphene 10 5 9 <![CDATA[Ti x THE 2x-1 ]]> 95 95 Graphene 5 5 10 <![CDATA[Ti x THE 2x-1 ]]> 80 80 Graphene 20 5
[0080] The process parameters of each embodiment are shown in Table 2.
[0081] Table 2 Process parameters of each embodiment
[0082]
[0083] In order to illustrate the relevant performance of the absorbent provided by the present invention, it is described in conjunction with the accompanying drawings.
[0084] Figure 1 This is the X-ray diffraction pattern of the TiO2 / carbon nanotube composite sample provided in Example 7. Figure 1 It can be seen that the physical phases of the sample are the expected TiO2 and carbon nanotubes, and the diffraction peaks of the spectrum are broad, indicating that the grain size of the material is small.
[0085] Figure 2 Ti provided in Example 7 x O 2x-1 / CNTs composite sample. Figure 2 Figure 2 Typical Ti x O 2x-1 ——Ti5O9 and Ti6O 11 The diffraction peaks of TiO2 indicate that the expected defective Ti is generated after reduction. x O 2x-1 .
[0086] Figure 3 This is a scanning electron microscope photo of the TiO2 / carbon nanotube composite sample provided in Example 7. Figure 3 The TiO2 / single carbon material composite absorbent is composed of round TiO2 particles uniformly wrapped around carbon nanotubes, wherein the size of TiO2 is between 5-20nm, and the diameter and length of the carbon nanotubes are 20nm and 1-10μm respectively, forming a dense core-shell structure.
[0087] Experimental verification shows that compared with TiO2 / carbon materials, Ti x O 2x-1 / Carbon composite absorbent has excellent microwave absorption capacity. Compared with TiO2, Ti x O 2x-1 It has better conductivity and narrower band gap, which is beneficial to improve its electromagnetic loss capability. This is because the hydrogenation temperature adjusts the oxygen vacancies and Ti in the TiO2 lattice. 3+ The high concentration of oxygen vacancies can capture the free electrons of neighboring Ti atoms, inducing the formation of Ti with lower valence 3+ , which eventually leads to Ti x O 2x-1 Abundant positively charged holes are generated in the CNTs, which are unique electric dipoles that can move under electromagnetic fields, causing conductivity losses. x O 2x-1 Many heterogeneous interfaces are formed between the two materials. The difference in Fermi levels between the two materials will generate electron transfer at the interface, resulting in a built-in electric field and a space charge region, which will affect the charge transport and interface polarization. At the same time, the difference in the dielectric properties of the two materials will lead to an uneven distribution of positive and negative charges, which will generate a space electric dipole moment and enhance polarization relaxation.
[0088] Figure 4 Ti provided in Example 7 x O 2x-1 SEM images of the / carbon nanotube composite sample. Figure 4 It can be seen that the Ti x O 2x-1 / Carbon material is composed of ellipsoidal Ti x O 2x-1 The particles are uniformly loaded around the carbon nanotubes, among which Ti x O 2x-1 The size is between 50 and 100 nm.
[0089] Figure 5 The schematic diagram of reflection loss of 30wt.% TiO2 / carbon nanotubes with a 2mm absorbing layer thickness is provided in Example 7. It can be seen that the reflection loss capability of the TiO2 / carbon nanotube composite material is relatively weak, with a peak value of only -8.5dB, which is far from meeting the absorbing requirements.
[0090] Figure 6 The absorbing layer thickness provided for Example 7 is 2 mm and 30 wt.% Ti x O 2x-1 / Schematic diagram of reflection loss of carbon nanotubes. Figure 6In the test, when the thickness of the absorbing layer is 2mm, the minimum reflection loss is -69.6dB, and the corresponding effective absorbing bandwidth is 4.0GHz: 9.0-13.0GHz. It is generally believed that RL = -10dB is the dividing point for measuring the performance of absorbing materials, because -10dB represents 90% absorption of electromagnetic waves, and the frequency band of absorbing materials with RL < -10dB represents the effective absorbing frequency band.
[0091] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
Claims
1. A titanium oxide / carbon material composite absorbent, characterized in that: The absorbent includes Ti x O 2x-1 As a substrate, and a carbon material composited on the substrate; x = 1 to 10; The content of the matrix is 50-99wt.%, the content of the carbon material is 50-1wt.%, and the sum of the percentages of the matrix and the carbon material is 100%.
2. The titanium oxide / carbon material composite absorbent according to claim 1, characterized in that: The carbon material is carbon fiber, carbon nanotube or graphene.
3. The titanium oxide / carbon material composite absorbent according to claim 1, characterized in that: The particle size of the carbon material is 1 to 10 μm; x O 2x-1 The particle size of the particles is 50 to 100 nm.
4. A method for preparing the titanium oxide / carbon material composite absorbent according to any one of claims 1 to 3, characterized in that: The following steps are involved: Dispersing tetrabutyl titanate, carbon material, acetic acid and concentrated nitric acid in anhydrous ethanol, stirring evenly to obtain a mixed solution; The mixed solution is transferred to a reaction kettle and kept at 160-200°C for 4-8 hours to obtain a TiO2 / carbon material precursor; The TiO2 / carbon material precursor is placed in a tubular furnace and kept warm at 800-1100°C for 2-8 hours in a hydrogen atmosphere to obtain a titanium oxide / carbon material composite absorbent.
5. The method for preparing the titanium oxide / carbon material composite absorbent according to claim 4, characterized in that: The dosage ratio of tetrabutyl titanate, carbon material, acetic acid, concentrated nitric acid and anhydrous ethanol is 1g: 0.01-2g: 10-20mL: 2-5mL: 40-60mL.
6. The method for preparing the titanium oxide / carbon material composite absorbent according to claim 4, characterized in that: The mixed solution is transferred to the reactor at a heating rate of 5 to 10°C / min.
7. The method for preparing the titanium oxide / carbon material composite absorbent according to claim 4, characterized in that: The TiO2 / carbon material precursor is placed in a tube furnace at a heating rate of 8 to 12° / min.
8. Use of the titanium oxide / carbon material composite absorber according to any one of claims 1 to 3 in electromagnetic absorption.
Citation Information
Patent Citations
Core-shell structured Ti4O7 / magnetic metal composite absorber and its preparation method
CN113423255B